Design of Modern Ammikal - G. ., SuryanagaRaju; R., Puviarasi (International Journal of Psychosocial Rehabilitation, 2020)
The ammikal is a traditional tool used to mix the various food spices together; now a days there are no ammikals due to electrical mixtures. There were not enough proteins and vitamins in the food that we are cooking at home. Due to the electrical mixture in the mixture, the vitamins and proteins present in vegetables are dissolved, and it becomes useless by losing the nutrients in the vegetables. This is a small issue, but from this issue only the imbalance is done in the human body.